1996
DOI: 10.1246/cl.1996.443
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Molecular Structure of 1,2-Dimethoxyethane Crystallized on a New Diffractometer

Abstract: Crystal and molecular structure of 1,2-dimethoxyethane (DME) with low melting point (−58 °C) was investigated by crystallization on a new imaging plate-Weissenberg type diffractometer with a new low temperature equipment. The crystal belongs to the monoclinic system and the space group is C2/c. There are four molecules in a unit cell. The DME molecule lies on a two-fold axis and has a TGT conformation in the crystalline state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…The crystal structure of G1 is known in which the G1 molecules adopt one of two conformations (tg + t or tg -t). 33 Solvate Structures and Ionic Association. In dilute solutions, electrolyte mixtures are typically modeled as consisting of highly solvated "free" ions.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of G1 is known in which the G1 molecules adopt one of two conformations (tg + t or tg -t). 33 Solvate Structures and Ionic Association. In dilute solutions, electrolyte mixtures are typically modeled as consisting of highly solvated "free" ions.…”
Section: Resultsmentioning
confidence: 99%
“…The geometries of the conformers of DME have been calculated previously, but no comparative discussions of the results by different calculation methods have been made. The calculated results may be compared with the experimental molecular geometries in crystals determined by X-ray diffraction; the molecule in crystals has been shown to assume the TGT conformation.…”
Section: Resultsmentioning
confidence: 99%
“…It is noticed that the CO−CC torsion angle in crystals differs by 7−8° from the angle theoretically calculated, apparently due to intermolecular interactions. The X-ray diffraction study has in fact shown the possibility of intermolecular interactions between the methyl group and the oxygen atom and between the methylene group and the oxygen atom …”
Section: Resultsmentioning
confidence: 99%
“…In the crystalline state DME does not pack in the usual side-by-side zigzag conformation preferred by the corresponding alkane (hexane) but rather in gauche conformations that expose the lone electron pairs of the two oxygen atoms towards the same direction. 20 The packing of diglyme in a crystalline phase is also not dominated by zig-zag (transoid) conformations or side-by-side arrangements but rather by an assortment of trans and gauche conformations, as attested by vibrational-dynamics and first-principle studies. 21 Such differences between DME or diglyme and the corresponding alkanes (hexane or nonane) in terms of chain-chain interactions may partially explain the different bulkiness of the observed non-polar domains.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%